Adaptation and validation of the All Aspects of Health Literacy Scale (AAHLS) in healthcare settings of Addis Ababa, Ethiopia - Tolasa Yadate; Eshetu Girma; Yordanos Tadesse; Tariku Dejene; Finina Abebe (BMC, 2024)
Abstract Background Since health literacy is known to be related to health outcomes, it should be measured to explain how it is associated with the health status of the population. Health literacy tools are designed to measure different dimensions of health literacy of individuals based on their objective. The AAHLS tool is comprehensive and can cover all aspects of health literacy. Overall in Ethiopia, there is no standard health literacy tool that has been developed or/and validated. Therefore, the aim of this study was to adapt and validate the All Aspects of Health Literacy Scale (AAHLS) in healthcare facilities in Addis Ababa city, Ethiopia. Methods A mixed-method, facility-based, cross-sectional study was conducted in Addis Ababa city from February 1, 2022, to May 30, 2022. The study was conducted in three phases: forward and backward translation and expert review, cognitive interviews and survey administration. For the cognitive interviews, a total of 16 participants and for the survey administration, 199 participants were involved. Coding and analysis of the qualitative data were performed using OpenCode 4.03 computer software. Then, pretesting (survey administration) was conducted to check the validity and reliability of the tool. CFA was conducted using SPSS version 26 and Stata version 14. Results and discussion The original three response categories were revised to five response categories based on the cognitive interview findings and expert reviews. The survey was administered to 199 participants, 55.8% of whom were males. The Kaiser‒Meyer‒Olkin measure of sampling adequacy was 0.685, with a significant difference according to Bartlett's test of sphericity (p < 0.001). After removing the empowerment factor model fit indices, the internal reliability and convergent and divergent validities improved. Confirmatory factor analysis showed that the model fit indices of the tool were satisfactory. The overall internal consistency, Cronbach's alpha, was 0.71. Conclusion The three response categories of the tool were revised to five response categories. The AAHLS tool was revised to include 10 items. The tool has exhibited adequate model fitness. The validated tool can be used for future health literacy assessments and interventions.